Secured bicycle parking rack for UiTM Pasir Gudang / Nurul Nurfaizzah Abdullah and Hazim Sharudin - Abdullah, Nurul Nurfaizzah; Sharudin, Hazim (School of Mechanical Engineering, 2022)
This project is about designing and fabricating a bicycle parking rack for UiTM Pasir Gudang. There are a few problems when the students bring their bicycle to the campus. There is no specific parking for the bicycles and so many cases of bicycle theft are reported in a year because of the lack of security for bicycles. To overcome these problems, this project will be designing a parking rack that can ease the bikers. In addition, the project will also fabricate a parking rack that is secured with a locking system to prevent bicycle theft.